Pengaruh Penggunaan Media Boneka Tangan Terhadap KemampuanBercerita Pada Anak TK - Raihani Akmalia Lubis; Afrilyana Afrilyana; Astania Radiva; Nirmala Anggraini; Noni Noni; Sherly Aprisi; Windi Asyriatul Husna (Jurnal Riset Psikologi, 2024)
The purpose of this study is to investigate whether children's storytelling skills are impacted by hand puppets. This study uses a one- group pretest- posttest design and is quantitative in nature. The population of Aisyiah 1 Bukittinggi Kindergarten was the subject of this investigation. In this study, a total of nine students were included in the random sampling process. The simple paired t-test was utilized as a data analysis tool. The paired simple t-test findings were determined to be worth. 000 based on the data processing results. The sig value in these results is more than. 005. This outcome demonstrates that children's storytelling skills are impacted by hand puppets.